Immunomodulatory Effects of Citrus Species Ethanol Extracts on Cellular Immune Responses in Wistar Rats and Mice - Yuandani, Yuandani; Wira Septama, Abdi; Rimayani Nasution, Lisda; Dwinanti, Debora; Putri Rambe, Dina; Ramadhani, Khairunnisa; Ramadhani Manurung , Wahidah (Trends in Sciences, 2024)
Currenty, Citrus reticulata has been found to modulate RAW 264.7 macrophage cell line. In the present study, the immunomodulatory effects of Citrus species peel extracts, including Citrus microcarpa, C. limon L., C. sinensis L. and C. hystrix were investigated on cellular immune responses in Wistar rats and mice. Mice were treated with ethanol extracts of Citrus species orally at dosages of 25, 50 and 100 mg/kg bw for 7 days. The phagocytosis activity of the extracts was examined using the carbon clearance method. Meanwhile, oral administration of Citrus species ethanol extracts at dosages of 17.5, 35 and 70 mg/kg bw was administered to Wistar rats to assess the effect of extracts on the delayed-type hypersensitivity (DTH) response using paw edema-method. Thin Layer Chromatography (TLC)-densitometry analysis was also performed. In both animal models, all extracts enhanced the cellular immune responses. Amongst the samples, C. sinensis, at the dose of 100 mg/kg bw in mice and 70 mg/kb bw in rats, demonstrated the highest stimulation on phagocytosis activity and DTH response, respectively. Except C. microcarpa, rutin was found in all Citrus species. The results indicate that Citrus species, particularly C. sinensis, have the potential to be developed into a potent immunostimulatory agent. HIGHLIGHTS The immunomodulatory effects Citrus species were investigated using mice and rats as animal models. Citrus microcarpa, C. limon, C. sinensis L. and C. hystrix were able to stimulate phagocytosis in mice and delayed-type hypersensitivity response in rats. Citrus sinensis demonstrated the highest stimulation on phagocytosis activity and delayed-type hypersensitivity response. Rutin was found in all Citrus species, except in microcarpa peels extract. GRAPHICAL ABSTRACT